2020
DOI: 10.1002/jmv.25656
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus detection and serotyping of fecal material collected from three children living on the outskirts of Belém city, Amazon region, Brazil, during the first 3 years of life (1983‐1986)

Abstract: In the current investigation, fecal material was obtained during a community‐based longitudinal study conducted from 1983 to 1986. This study consisted of 71 children aged newborn to 3 years. A total of 216 samples from three of these children were screened by real‐time quantitative polymerase chain reaction (RT‐qPCR) for the presence of enteroviruses, and positive samples were serotyped by VP1 and VP3 sequencing of the viral genome. Of these, 12 (5.6%) came from symptomatic cases, and the remaining asymptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
4
6
0
Order By: Relevance
“…In general, we were able to identify EV type in 78.3% (36/46) of the samples, which revealed a detection pattern EV-B (61.1%; 22/36) > EV-C (25%; 9/36) > EV-A (13.9%; 5/36) (Table 2 ). These findings were similar to previous reports that showed EV-B species more frequently detected than EV-C and EV-A species in children with AGE [ 18 20 ]. Some EV positive samples in rRT-PCR could not be typed (8/46; 17.4%) due to failure to produce amplicons.…”
supporting
confidence: 93%
“…In general, we were able to identify EV type in 78.3% (36/46) of the samples, which revealed a detection pattern EV-B (61.1%; 22/36) > EV-C (25%; 9/36) > EV-A (13.9%; 5/36) (Table 2 ). These findings were similar to previous reports that showed EV-B species more frequently detected than EV-C and EV-A species in children with AGE [ 18 20 ]. Some EV positive samples in rRT-PCR could not be typed (8/46; 17.4%) due to failure to produce amplicons.…”
supporting
confidence: 93%
“…This study demonstrated a high prevalence (76.5%) of picornavirus in human feces, and a relevant factor of this finding is the fact that some of the samples were older (>30 years), in addition to being of children who lived in peripheral regions and who had precarious basic sanitation conditions. Moreover, the detection of EV was a preponderant factor for the high rate found, since its prevalence was the highest among the viruses studied, corroborating preliminary studies carried out in this same region, where a prevalence of 63% of EV was obtained in fecal samples of children under 3 years old 37 …”
Section: Discussionsupporting
confidence: 86%
“…AiV/SalV, five (2.1%) of the 234 samples tested by RT-qPCR were positive, with high C t values(32)(33)(34)(35)(36)(37)(38). However, they were negative in nested PCR, avoiding sequencing and characterization of these samples for the presence of human Kobuvirus and Salivirus.…”
mentioning
confidence: 99%
“…Furthermore, even though the occurrence of infection by a single EV-type can result in severe clinical syndromes, the EV-coinfection can lead to increased possibility of developing complications and severe clinical aspects of disease [27]. Interestingly, previous work have demonstrated that the co-circulation of a high number of different NPEV types can favors recombination events as well as the emergence of the atypical clinical presentations and the severity of disease [28][29][30][31][32]. Additionally, the cross-neutralizing antibodies against different EV-types is not commonly observed, mainly in children ≤ 6 years [32].…”
Section: Discussionmentioning
confidence: 99%